The use of compact surveillance radar to study polar bears (Ursus maritimus) near Churchill, Manitoba, Canada - Cocksedge, Amy Grace (2021)
Many species of wildlife are currently facing intense competition with people for space and resources, resulting in increasing levels of human-wildlife conflict. In Canadas North, climate change is exacerbating this issue for polar bears (Ursus maritimus) and people. Unfortunately, scientific understanding of the factors that influence human-polar bear conflicts is substantially less developed for polar bears compared to other bear species. The majority of movement data on polar bears is accumulated from GPS tracking collars which is female-biased and has insufficient spatial and temporal resolution to document fine-scale movements. To address this shortcoming, my study tested the efficacy of compact surveillance radar (CSR) as a detection method and as a method to study polar bear movement and behaviours. The results showed that the radar currently functions adequately as a detection method, but with future improvements to the technology and customization by the user it has high potential to function as an autonomous detection and alert method. It also provides high-quality data on bears local movements that can be combined with resource and environmental data specific to the time and location of bear sighting. Though improvements are needed, CSR is a viable new technology to be integrated into polar bear management and ecological studies.